An approach to acanthosis nigricans - Meghana Madhukar Phiske (Wolters Kluwer Medknow Publications, 2014)
Acanthosis nigricans (AN) is characterized by dark, coarse and thickened skin with a velvety texture, being symmetrically distributed on the neck, the axillae, antecubital and popliteal fossae, and groin folds, histopathologically characterized by papillomatosis and hyperkeratosis of the skin. A high prevalence of AN has been observed recently. Different varieties of AN include benign, obesity associated, syndromic, malignant, acral, unilateral, medication-induced and mixed AN. Diagnosis is largely clinical with histopathology needed only for confirmation. Other investigations needed are fasting lipoprotein profile, fasting glucose, fasting insulin, hemoglobin and alanine aminotransferase for obesity associated AN and radiological investigations (plain radiography, ultrasonography, magnetic resonance imaging/computerized tomography) for malignancy associated AN. The most common treatment modalities include retinoids and metformin.